Analisis Kelayakan Investasi Terhadap Penyewaan Alat Berat pada PT.Tri Daya Jaya Makassar - Muhtazib Muhtazib; Muhamad Rifaldi (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
The aims of this research are to analyze the feasibility of PT. Tri Daya Jaya Makassar company engaged in heavy equipment rentalsto add investment in the form of adding vehicles.The analytical methods usedNet Present value, Internal Rate Of Return, Profitability Index, and Payback Period.The result of Investment Feasibility with the Net Present Value (NPV) shows that the total Cash Flow PV is Rp. 44,790,364,139 while the total investment proposed by the company is Rp. 35,534,195,000and the result of Net Present ValueisRp. 9.256.169.139. Whereascalculation of Internal Rate Of Return (IRR), it appears that the IRR value is 21.27%. So the DF value is 12%. Then the value of Probability Index (PI) 1.26 indicating PI> 1. It can be concluded that investment is feasible